Modeling and Simulation of Pump Storage Based on Indirect Field Oriented Control - Othman Hassan Abdalla; Minxiao Han (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper derived the mathematicalmodel of indirect field oriented control (IFOC) applied in pump storage toobtain the variable speed. The two identical seven level H-bridge multilevel converters connected in cascade have been used togenerate 6KV on the rotor side. The inputof power cell of H-bridge cascaded multilevel converter fed from a phase-shifttransformer to reduce the total harmonic distortion of rotor currents. The slip angle of doubly fed asynchronousinduction machine is calculated by using the stator flux of indirect fieldoriented control (IFOC). Theslip angle calculated is used to control of variable speed of the pump storagebased on machine parameters. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3357